Facilities for Medico Legal Autopsy in India – Awareness among Doctors and Infrastructure Available (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
Every doctor in the government set-up is bound by duty to perform medico legal autopsy, especially in the rural areas, where experts in the field are not available. The following study was undertaken to adjudge the awareness of the doctors involved in this work towards their duty and to study the infrastructure provided by the government for the conduct of these autopsies in different categories of hospitals across the country.
Keywords: Mortuary; Medico-legal autopsy; Autopsy block; Autopsy room; Mobile Autopsy Unit